Implementasi R Software Untuk Prediksi Curah Hujan (Perbandingan ARMA dan ARIMA) - Parhusip, Jadiaman (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Rainfall or weather conditions that occur in a particular area can basically be calculated, orpredicted. X district is an area that is frequently flooded during the rainy season. Forecasting rainfall canhelp governments and communities in taking flood precautions [1]. In this study, forecasting rainfall inthe district of X, is done by using time series method approach. To perform forecasting rainfall, used twomethods, ARMA and ARIMA. Furthermore, the results of both methods are compared with the actual datato determine which method is most closely with real data. The conclusion of this study is the method ofARMA (1,1) forecasting results are closer to the real data [2].